1977
DOI: 10.1530/acta.0.0840011
|View full text |Cite
|
Sign up to set email alerts
|

Transitory Growth Hormone Deficiency Successfully Treated With Human Growth Hormone

Abstract: This study was carried out in order to determine whether children with a transitory type of growth hormone deficiency showed an accelerated growth in height velocity on treatment with human growth hormone (HGH). Following careful diagnostic routine procedures 13 extremely short children were diagnosed as having isolated growth hormone deficiency, and were successfully treated with HGH. A true isolated growth hormone deficiency was present in 5 of the children, whereas 8 showed a normal increase in serum growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1982
1982
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Comparable findings in single cases had been reported already in 1971 and 1972 [63,192]. Later Trygstad [296] and Kastrup et al [130] described the normalisation of previously insufficient GH-increases in the ITT after longterm treatment with GH and--which was probably more important--onset of puberty.…”
Section: Growth Hormonementioning
confidence: 53%
See 1 more Smart Citation
“…Comparable findings in single cases had been reported already in 1971 and 1972 [63,192]. Later Trygstad [296] and Kastrup et al [130] described the normalisation of previously insufficient GH-increases in the ITT after longterm treatment with GH and--which was probably more important--onset of puberty.…”
Section: Growth Hormonementioning
confidence: 53%
“…The observation of Pierson and Deschamps [197], that growth velocity during the first 4 to 5 years of life would usually correspond to the average and fall to lower values thereafter is not confirmed by other authors. Weight gain follows the same trend as growth in height [205,206,296]. Particular leanness as claimed by Karp et al [128,129] has not been observed by other investigators [24,197].…”
Section: Clinical Aspectsmentioning
confidence: 87%
“…It has been recognised for many years that children with constitutional delay of growth and puberty (CDGP) show a transient hGH suppression which has led several clinicians to use hGH in their treatment [30][31][32], These children were generally started on treatment with a diag nosis of hGH deficiency based on lack of response to pharmacological tests and their height velocities in creased, even on low doses of hGH (8-12 U/week). A decrease in physiological hGH secretion has been shown to occur in CDGP which continues up to pubertal stage 3 [33].…”
Section: Constitutional Delay Of Growth and Pubertymentioning
confidence: 99%
“…However, insufficient numbers of patients, different therapy durations, and changes in the time of the dosage prescribed, due, in particular, to a greater availability of the hormone, have led to different results (10,11). In addition, the modifications recently made in the therapy schedule and administration route, as well as the uncertainties of the diagnostic criteria indicating the subjects to be treated (13)(14)(15)(16)(17)(18)(19)(20)(21), will probably further change the final results of the treatment. It is certain, however, that the experience acquired to date has not enabled us to adopt an optimal therapeutic approach, either for the single patient or for the whole group, casting doubt on the auxological outcome of the patients treated.…”
Section: Introductionmentioning
confidence: 99%